Measuring meaning in life following cancer - Jim, Heather S. (2006)
Meaning in life is a multi-faceted construct that has been conceptualized in diverse ways. It refers broadly to the value and purpose of life, important life goals, and for some, spirituality. We developed a measure of meaning in life derived from this conceptualization and designed to be a synthesis of relevant theoretical and empirical traditions. Two samples, all cancer patients, provided data for scale development and psychometric study. From exploratory and confirmatory factor analyses the Meaning in Life Scale (MiLS) emerged, and includes four aspects: Harmony and Peace, Life Perspective, Purpose and Goals, Confusion and Lessened Meaning, and Benefits of Spirituality. Supporting data for reliability (internal consistency, test–retest) and construct validity (convergent, discriminant, individual differences) are provided. The MiLS offers a theoretically based and psychometrically sound assessment of meaning in life suitable for use with cancer patients.